Pengaruh Lama Penyimpanan Dekok Daun Sirih Hijau (Piper betle l.) terhadap Aktivitas Daya Hambat Bakteri Streptococcus agalactiae Penyebab Matitis pada Sapi Perah - Oki Selfiana Marsono; Tri Eko Susilorini; Puguh Surjowardojo (Faculty of Animal Science Universitas Brawijaya, 2017)
ABSTRACT This research was conducted from January to February 2017 at Microbiology Laboratory, Faculty Science and Technology, Islamic Maulana Maliki Ibrahim University, Malang and at Microbiology Laboratory, Faculty of Science, Muhammadiyah University, Malang. The purpose of this research was to determine the effectiveness of Piper betle L. leave extract on antibacterial activity the growth of Streptococcus agalactiae. The method used was Complete Randomized Design (CRD) with 8 treatments and 6 replications. Piper betle L. leaves extract was used 20% for P0 (0-day), P1 (first day), P2 (second day), P3 (third day), P4 (fourth day), P5 (fiveth day), P6 (sixth days) and P7 (seventh day). The results showed that Piper betle L. leaves extract had a highly significant effect (P<0.01) on inhibiting the growth of the bacteria so the results were continued with LSD test analysys because there were differences among variables. The results showed that P0 was the highest (3.93±0.50); then followed by P1 (3.83±0.69); P2 (3.47±0.21); P3 (3.13±0.22); P4 (3.12±0.58); P5 (3.04±0.24); P6 (3.00±0.44) include at medium categories, and P7 (2.97±0.19) include at low category, where inhibition zone which formed on each treatment have non significant decreased. In conclusion, the storage of Piper betle L. extract have effect on antibacterial activities (Streptococcus agalactiae), which the highest at day-0.